Rekayasa Sistem Tata Kelola Dan Layanan Mobile Proses Perkuliahan - Adi Chandra Syarif; Farif Hartono Gunawan; Erick Alfons Lisangan (Fakultas Teknologi Informasi, Universitas Atma Jaya Makassar, 2016)
Learning management system, as part of higher education governance, is the process of organizing, planning and supervising the implementation of curriculum in order to achieve the learning objective (LO). PP No. 19 in 2005 and No. 32 in 2013 set the standard for higher education governance quality assurance systems where Internal Quality Assurance System is requiredfor higher education institutions that aim to achieve continuous improvement. The main problem in implementing internal quality assurance is that to achieve continual improvement we need an effective supervision that not only can provide data on the results of implementation but more importantly is the data to the process itself. Generally universities has implemented a system of governance and supervision that rely on the outcome of the process but not how the process done. Meanwhile, in order to achieve continuous improvement required a monitoring and evaluation system that does not rely solely on the output but also data from process. This research aims to develop a system of governance with data and information services to the passage of the academic process, especially at the University of Atma Jaya Makassar. This study uses an object oriented approach with UML design method by utilizing the computer network architecture for wireless and mobile technology as key technology. This research produced a system with the ability to monitor the passage of the lecturing process in realtime in order to improve monitoring, evaluation and quality processes in a structured lectures and concurrent transparent, accountable and responsive.